RESPEK and PROSPEK: Welfare Approach by the Government to Overcome Vertical Conflict in Papua - Jeihany Anggrilla Safarani; Agus Adriyanto; Herlina Juni Risma Saragih (CV. Rayyan Dwi Bharata, 2023)
The dynamics of separatism in the land of Papua and its threats to Indonesia are important issues that have created complex conflicts. One of the efforts to reduce the escalation of the Papua conflict is through empowerment efforts. Empowerment is one part of the implementation of RESPEK and PROSPEK by the Papua regional government. RESPEK and PROSPEK are efforts to increase public awareness of the threat of separatism and increase their participation in the development process. RESPECT is run by soft power created to balance military power (hard power) in the long term to improve welfare. This study uses a qualitative approach in the type of literature with data processing originating from document sources and library materials. The results of the study show that the welfare approach is directly related to the human dimension. Programs implemented on the basis of RESPEK and PROSPEK directly benefit local communities (OAP) so that there is an equal distribution of human needs. These programs have a budget allocation for special autonomy funds transferred by the central government to the Papua provincial government every year. In addition, they are implemented by prioritizing the involvement of village heads to increase participation and consensus between parties. This strengthens the government's image of OAP perceptions so as to diminish the influence of the roots of separatism in Papua.